Interrelationship between Military Pedagogy and Military Psychology (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
Military pedagogy and military psychology are two closely interconnected scientific fields that jointly support the effective training, education, and development of military personnel. Military pedagogy focuses on the organization, methods, and content of educational processes within military institutions, while military psychology studies the mental processes, behavior, emotional stability, and psychological readiness of servicemen. Their interaction ensures not only the transfer of professional knowledge and skills but also the formation of psychological resilience, discipline, leadership qualities, and motivation. This paper analyzes the theoretical and practical links between these two disciplines, emphasizing their integrated role in enhancing combat readiness and professional competence in modern armed forces.
Keywords: Military pedagogy; military psychology; professional training